2008
DOI: 10.1088/0256-307x/25/4/058
|View full text |Cite
|
Sign up to set email alerts
|

A Power Interruption Technique for Investigation of Temperature Difference in Stabilized Low Direct-Current Arc Burning in Pure Argon on Atmospheric Pressure

Abstract: Plasma of argon stabilized arc column, in a current range 3-11 A, is investigated using emission spectrometric diagnostic techniques. Temperatures are evaluated using several methods: argon line to adjacent recombinational continuum intensity ratio, absolute emissivity of argon line, measurement of electron number density, and power interruption. Electron number density is evaluated from absolute emissivity of recombinational continuum. The difference between electron Te and heavy particle T h temperature rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our previous results [31] have shown that the presence of water vapour, and small concentrations of KCl induce changes of plasma parameters mainly in the peripheral arc zones. However, these changes will inevitably affect the properties of the central part of the discharge.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous results [31] have shown that the presence of water vapour, and small concentrations of KCl induce changes of plasma parameters mainly in the peripheral arc zones. However, these changes will inevitably affect the properties of the central part of the discharge.…”
Section: Resultsmentioning
confidence: 84%
“…It was found that the addition of water produces a small lowering of the arc axis temperature and electron density. Presence of 0.5 % KCl brings additional temperature lowering and reduction of electron number density [13,31]. Although the net effects of water and small concentrations of EIE on plasma parameters are essentially the same, the mechanisms behind these changes are somewhat different.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the relatively long horizontal part of the arc column makes it suitable for atomic absorption measurements, especially for elements that form refractory oxides [13]. In this source, fast responses of spectral line intensities to power interruption were studied for a number of atomic species, to get a better insight into the different excitation mechanisms that occur in the arc plasma [14], and also to get information regarding the state of thermodynamic equilibrium [15][16][17]. A power modulation method was used to investigate delayed responses of argon and hydrogen spectral lines and also of continuum radiation [18].…”
Section: Introductionmentioning
confidence: 99%